THE FORMATION OF LEADERSHIP OF CADET AT MILITARY ACADEMY - Tahirov, Rashad (Revista Gênero e Interdisciplinaridade, 2020)
The article discusses the features of the formation and development of leadership qualities in cadets studying at Military Academy. Referring to the literature are explained the basic concepts of leadership including military leadership, the differences between a leader and manager, the need to form leadership qualities in officer and a set of these qualities. The article higlihts on the required conditions, pedagogical and organizational, the usage of which will make the process of formation and development of leadership qualities among the cadet more effective.